SOSIALISASI DAN PELATIHAN PENGGUNAAN MESIN PEMBERI PAKAN IKAN TAWAR OTOMATIS BERBASIS IoT DI KOLONG BEKAS PENAMBANGAN TIMAH DI KABUPATEN BANGKA - Sulistyo, Eko; Dwisaputra, Indra; Ocsirendi, Ocsirendi; Tumatul Ainin, Dewi; Buulolo, Martinus; Juanda, Juanda; Ramli, Ramli (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the efficiency and productivity of freshwater fish farming in former tin mining pits through the socialization and training on the use of Internet of Things (IoT)-based automatic feeding machines. The activity was carried out in Bangka Regency and involved 20 local fish farmers who had previously relied on manual feeding methods. The program began with an introduction to the concept and benefits of IoT technology in the fisheries sector, followed by theoretical training and hands-on practice using the automatic feeding machine, as well as an evaluation of the training outcomes through pre-tests and post-tests. The evaluation results showed a significant increase in participants' understanding of IoT technology, with an average improvement of 87%, rising from 13% prior to the training. Participants also demonstrated better comprehension of how the automatic machine works and enhanced their ability to operate it independently. The IoT-based automatic feeding machine has proven effective in increasing time efficiency, reducing feed waste, and enabling remote monitoring via mobile devices. This community service initiative is expected to be a starting point for technological transformation in aquaculture practices in post-mining areas, moving towards a more modern, productive, and sustainable system.